2003
DOI: 10.1149/1.1532328
|View full text |Cite
|
Sign up to set email alerts
|

Radical Formation in Hydroxylamine-Copper Chemical Mechanical Planarization Processes

Abstract: Hydroxylamine is commonly employed in laboratory chemistry as a reducing agent, such as for reduction of Cu͑II͒ to Cu͑I͒, yet a sulfate salt oxidizes copper during chemical mechanical planarization ͑CMP͒ processing employed in the manufacture of semiconductors. Electrochemical, Fourier transform infrared, and electron paramagnetic resonance measurements were conducted to verify formation of a nitrosyl radical complex, similar to Fremy's salt, that is believed to be the molecular species responsible for catalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…The data of Table X indicated that Cu 2 O was abundant at pH 3.5 while CuO/Cu͑OH) 2 was abundant at pH 7.5. Previous measurements 25 demonstrated that the redox potential for HAS at pH 3.5 was 0.65 V so that the 0.52 V reduction of Cu͑I͒ to Cu͑0͒ was indicated. At pH 7.5, the redox potential for HAS ͑hydroxylamine͒ was only 0.26 V, insufficient to reduce copper oxide.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The data of Table X indicated that Cu 2 O was abundant at pH 3.5 while CuO/Cu͑OH) 2 was abundant at pH 7.5. Previous measurements 25 demonstrated that the redox potential for HAS at pH 3.5 was 0.65 V so that the 0.52 V reduction of Cu͑I͒ to Cu͑0͒ was indicated. At pH 7.5, the redox potential for HAS ͑hydroxylamine͒ was only 0.26 V, insufficient to reduce copper oxide.…”
Section: Discussionmentioning
confidence: 96%
“…͑See the discussion on the XPS data later in this section.͒ Hydroxylamine is a strong reducing agent capable of removing the oxide layer from the copper wafer surface, but in the presence of unoxidized copper metal, and certain other metals, HAS is catalytic for radical oxidation of the metal. 25 The chemical composition of a copper surface film is affected by air oxidation, chemical oxidation, and parasitic passivation reactions represented by the following equations as …”
Section: Discussionmentioning
confidence: 99%
“…Sodium based solutions can not be used for actual semiconductor processing due to contamination issues. However, in order to understand the electrochemical aspects of metal dissolution in slurry chemicals, salts such as Na 2 SO 4 , NaNO 3 and NaClO 3 have been used as supporting electrolytes to reduce the solution resistivity [10,14,[21][22][23][24]. A kink was observed in the anodic branch of the plot for solutions containing hydrogen peroxide concentration of less than 0.5%.…”
Section: Cmp Experimentsmentioning
confidence: 99%